Construction of a Novel Ferroptosis-Related Gene Signature of Atherosclerosis - Huang, Tucheng; Wang, Kangjie; Li, Yuewei; Ye, Yanchen; Chen, Yangxin; Wang, Jingfeng; Yao, Chen (Frontiers in Cell and Developmental Biology, 2022)
Atheroclerosis refers to a chonic inflammatory disease that is featured by the accumulation of fibrofatty lesions in the intima of arteries. Cardiovasular events associated with atherosclerosis remains a major cause of mortality worldwide. Recent studies indicated the ferroptosis, a novel programmed cell death, might participate in the process of atherosclerosis. However, the ferroptosis landscape is still lacking. In this study, 59 genes associated with ferroptosis were ultimately identified in atherosclerosis intima. GO and KEGG pathway enrichment annlysis were performed for functional annotation. Through the construction of PPI network, 5 hub genes (TP53, MAPK1, STAT3, HMOX1, PTGS2) were then validated histologically. The ceRNA network of hub genes were ultimately constructed to explore the regulatory mechanism between lncRNAs, miRNAs and hub genes. This finding provide more insight into the ferroptosis landscape and protentialy therapeutic target of atherosclerosis.